Merancang Loyalitas Pelanggan Melalui Pengalaman dan Keterikatan Emosional: Studi pada Bakmi Chao Guo Kota Malang - Naufal Ahnaf; Choirul Anam; Wahju Wulandari (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of customer experience on customer loyalty mediated by emotional bonding in Bakmi Chao Guo customers in Malang City. In a highly competitive culinary industry, customer loyalty is one of the important elements in maintaining and improving business continuity. Bakmi Chao Guo, as one of the culinary business actors, already has a number of regular customers who make regular visits every quarter. However, the number of visits still does not reach the company's optimal target, which is 450 visits per quarter. This shows that despite the presence of loyal customers, a more appropriate strategy is still needed to significantly increase the frequency of visits. This study uses a quantitative approach with a survey method of 120 respondents who are active customers of Bakmi Chao Guo. The data analysis technique used is Structural Equation Modeling–Partial Least Square (SEM-PLS) to test the relationship between research variables, namely customer experience, emotional bonding, and customer loyalty. The results of the study show that customer experience has a positive and significant influence on customer loyalty, both directly and indirectly through the mediation variable of emotional bonding. A fun and memorable customer experience creates a strong emotional bond, which ultimately encourages customers to stay loyal and make repeat purchases. These findings provide important managerial implications for Bakmi Chao Guo managers and other culinary business actors, namely the need to focus on creating consistent, personalized, and meaningful customer experiences. In addition, building a close emotional connection between customers and brands will be a decisive factor in creating sustainable long-term loyalty amid ever-evolving market competition.